Answer
First you would divide both sides by 2y so it would be
x/2y = z
Step-by-step explanation:
Answer:
The equation of the quadratic function shown is;
x^2+ 2x -3
Step-by-step explanation:
Here in this question, we need to know the quadratic equation whose graph was shown.
The key to answering this lies in knowing the roots of the equation.
The roots of the equation are the solution to the quadratic equation and can be seen from the graph at the point where the quadratic equation crosses the x-axis.
The graph crosses the x-axis at two points.
These are at the points x = -3 and x = 1
So what we have are;
x + 3 and x -1
Multiplying both will give us the quadratic equation we are looking for.
(x + 3)(x-1) = x(x -1) + 3(x-1)
= x^2 -x + 3x -3 = x^2 + 2x -3
Answer:
6
Step-by-step explanation:
Constants are any numbers that don't change.
2x + 3y + 6
Since "6" is the only number here, that is the only constant.
Best of Luck!
Answer:
commutative
Step-by-step explanation:
you are typing the same numbers but in different order
If Jamerra pays $450 simple interest in 2 years,
she will pay (450/2) = $225 simple interest each year.
225 / 3000 = 0.075 = 7.5 %